Design of graphene-based multi-input multi-output antenna for 6G/IoT applications - Reem Hikmat Abd; Hussein Ali Abdulnabi (Institute of Advanced Engineering and Science, 2023)
In the future, 6G wireless communications will be integrated into various applications. It is expected that it will handle all Internet of Things services as well as satellite communications. Additionally, it is predicted to support machine learning (ML) and artificial intelligence (AI). So this work investigated four orthogonal ports graphene-based multiple-input and multiple-output (MIMO) antenna in the terahertz frequency regime. With wide-band (7.1-13) THz, minimum return loss close to -30 dB and a good isolation value. That was designed over silicon dioxide (Sio2) 100×100 substrate with a thickness of 10 µm and a maximum gain reaching 8.3 dB at 11 THz. By adjusting the provided DC voltage, the chemical potential of graphene can be tuned, which in turn allows for the MIMO antenna characteristics to be changed. Envelop correlation coefficient (ECC) and diversity gain (DG) were investigated for the presented design. In addition, these values were determined to assess compatibility and difficulties connected with communication over a short distance. The geometry of the MIMO antenna is adaptable to various applications in the THz band with highperformance requirements, such as sensing, scanning for security threats, biomedical applications, wireless communication systems with high speed built on the 6G standard, and the internet of things (IoT).